If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 9 = -7 + -5x Reorder the terms: 9 + -1x = -7 + -5x Solving 9 + -1x = -7 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 9 + -1x + 5x = -7 + -5x + 5x Combine like terms: -1x + 5x = 4x 9 + 4x = -7 + -5x + 5x Combine like terms: -5x + 5x = 0 9 + 4x = -7 + 0 9 + 4x = -7 Add '-9' to each side of the equation. 9 + -9 + 4x = -7 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = -7 + -9 4x = -7 + -9 Combine like terms: -7 + -9 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| 2=v-3/3 | | 1/5x-3=4 | | -5w^2+8=0 | | T/-2=18 | | 2(2x+5)-3=-3(x-1) | | 3x-2/3=7 | | 2x+9y-36=180 | | c(x)=x-4/x^2-16 | | -17=n-20 | | 4nm-4m=8 | | 17+2n=2n+21 | | 24=(3-n)+5 | | 1w=-11 | | x-18.1=-0.7 | | 0.01(1)+0(-0.5)=0.02(-0.5)+1 | | 6x+55=3x+244 | | m^3=8/125 | | j-3/2=2 | | -8+3.5=1-4(3.5) | | -3n+18=-6(n+1) | | 12x-34=46+7x | | 12b=.2 | | (6g-9)+1/3(15-9g)= | | 12+3d=d | | 5.7+b=23 | | -4x+82=-86-10x | | 25=n-(3) | | R^2=-96 | | (0.01)(1)+0x=0.02(x+1) | | 24x^2-58x+40=7 | | 2/3y-12 | | 17=-d |